Decoding depression: insights into molecular biomarkers and neuroimaging of depression - Reema Almadodi; Aimi Syamima Abdul Manap (Penerbit Universiti Kebangsaan Malaysia, 2025)
In this review, we explore the recent insights on major depressive disorder (MDD) and emphasizes the involvement of specific genes, particularly in MDD development. The paper consolidates and examines various biological, epigenetic, and environmental factors contributing to depression, illustrating the intricate interplay among these elements. Interestingly, molecular and neuroimaging findings are summarized and discussed, acknowledging the current absence of reliable biomarkers for MDD. This absence is attributed to the structural and functional complexity of the brain, the limitations of available technology, and the weak correlations between genetic markers and clinical manifestations of depression. Interestingly, in somatic treatment, only electroconvulsive therapy (ECT) has been proven effective in treating resistant depression. In conclusion, this article critically reviews the molecular biomarkers and neuroimaging of depression. Existing mechanisms such as the biogenic amine hypothesis and genetic and environmental factors are recognized for explaining depression’s pathophysiology. The potential for neuroimaging and molecular studies to yield promising biomarkers for depression is highlighted.